Traditional leadership and social support in Southern Malawi - Margolies, Amy; Aberman, Noora-Lisa; Gelli, Aulo (International Food Policy Research Institute, 2017)
This study presents qualitative findings on the dynamics of household and community resources for food security and nutrition in Southern Malawi. We explore how kinship and social obligations influence the allocation of social support, and focus on the role of village chiefs. We then examine the implications for state- and donor-led social programs in light of the norms that permeate village life.